“Diferencia en la liquidación de bienes muebles e inmuebles en la sociedad conyugal en la legislación ecuatoriana” - Poma Moreno, Diego Marcelo (2017)
The investigation called: "DIFFERENCE IN THE LIQUIDATION OF MOVABLE AND IMMOVABLE PROPERTY IN THE SPOUSAL SOCIETY IN THE ECUADORIAN LEGISLATION." It has dealt with issues of marriage, the conjugal society, the dissolution of the conjugal society and the liquidation of the conjugal society, the dissolution and liquidation within the de facto union. The economic effect of marriage and the de facto union is to create a partnership, in which all the goods acquired or, in turn, all the debts contracted by both are acquired or even when only one of the they contract it, because according to the law they have the status of joint debtors. However, there are factual situations in which it becomes necessary to dissolve the conjugal partnership or de facto union, which is why the Civil Code establishes the possibility that the couple or the spouses may voluntarily dissolve and / or agree to the conjugal partnership or the de facto union may even be dissolved in a contentious and unilateral manner. When the spouses wish to remain married this can subsist perfectly in spite of existing the dissolution of the conjugal society or the de facto union. Finally, this research analyzes the way in which the issue of the liquidation of the conjugal partnership and the de facto union is defined, which corresponds to the partition of the acquired assets, making a distinction between the settlement of movable and immovable property. At the same time we can say that for the liquidation it must be settled according to its nature, based on the Ecuadorian legislation.